Juliet of the Tropics: A Bilingual Edition of Alejandro Tapia y Rivera’s La cuarterona (1867). Tr. John Maddox. Cambria Press, 2016. - Anibal Gonzalez Perez (Latin American Literary Review, 2021)
Review of a recent English translation of Alejandro Tapia y Rivera's play La cuarterona.